A Case Study and Analysis of Information Theory and Coding - Sharma, Pratibha (Journal of Advanced Research in Information Technology, Systems and Management, 2021)
The main objective of the paper to talk about advantage and knowledge domain of the analog feedback communication and estimate similarities or dissimilarities between the two things which come near to their and digital communication system optimization. There is shown extreme differences between mathematical devices used for detailed examination of the element and optimization of analog feedback communication and digital communication system which officially allow to do something to look attentively at the approaches to their optimization as free from outside control directions of research in information theory[1]. The main cause of disagreement is calculable disagreement of the source of signal transmitted by the system. Both the system analog feedback communication and digital communication system solve the same task by using completely dissimilar methods. The outcome of detailed examination of the element show the digital communication system are impossible for the digital signal transmission. In whatever way,   who’s optimal in analog feedback system can be relevant, they transmit analog signal with the greater power bandwidth quality than digital communication system designed for same application. How to cite this article: Sharma P, Mirani S. A Case Study and Analysis of Information Theory and Coding. J Adv Res Info Tech Sys Mgmt 2020; 4(1): 5-8